The Benefits of out-of-class English Exposures on Undergraduate Students' English Mastery - Wina Chandrella (Surakarta English and Literature Journal, 2023)
This research aims to determine the benefits of outside-classroom English Exposure on undergraduate students’ English mastery. This research involves 50 undergraduate students from batch 2017-2019 filling out a questionnaire related to English Exposures that they have gotten outside the classroom. Through the analyzed questionnaire, 5 undergraduate students were chosen for the interview to have deeper information. Considering the pandemic situation, the discussions were done by using Zoom meetings. The findings showed that English Exposure was beneficial for undergraduate students’ English mastery. The benefits were the improvement of undergraduate students’ pronunciation, grammar, vocabulary, listening skills, etc. From the study, YouTube was the most popular platform where undergraduate students got English Exposure since it had many videos that elicited students’ interest. Looking at the benefits of English Exposure, teachers should combine their lessons with contemporary media to improve students’ English mastery and spark students’ interest in English lessons.